SPORT SHÍNÍǴÍWLARÍNÍŃ TÁSIRIN ANÍQLAYTUǴÍN JAǴDAYLAR - Bekmurzaev, A.K. (SCIENCE and SOCIETY, 2025)
This article talks about the diverse effects of sports and physical exercises on the body, exercise techniques, as well as the pedagogical classification of sports and physical exercises.
Keywords: sports; physical culture; exercise; technique; system; hygiene